Traditional Colombian Games in Virtual and in-Person Education - RAMÍREZ AVENDAÑO, ALBERTO; AVELLA GUTIÉRREZ, JOHANNA MILENA; RINCÓN SILVA, MARÍA PAULA (Universidad Pedagógica y Tecnológica de Colombia, 2022)
The main object of this research study was to enhance the Communicative Competence of fifth graders through the use of traditional Colombian games in virtual and in-person settings in an EFL classroom. The participants of this research study were thirty-three (33) students from a public school in Tunja, Boyacá, Colombia. This study is framed as qualitative Action Research. The methodological procedure implemented to collect data was based on the application of seven (7) workshops based on traditional Colombian games where the students were able to strengthen their Communicative Competence and use language in authentic school contexts, virtually and in-person classes. Three different instruments were taken into account in order to collect data: Video recordings, semi-structured interviews and a field journal. The findings of this research study revealed that the use of traditional Colombian games developed the Communicative Competence of the students, giving them tools to communicate in an authentic school context and not only during the development of the workshops but from now on as well. Regarding the motivation, it was evident that being able to interact with their classmates and teachers during the implementation of the games, made the students feel more comfortable and willing to participate in the activities proposed. Finally, the versatility of the workshops is a useful tool that allows us to cover much more topics, levels of language and settings (virtual and in-person) than usual